On the Terminological Mistake in the Biography of the Astrakhan Cossack Regiment Commander, Major General P.S. Popov - Astafyev Evgeniy V. (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2016)
On the basis of authentic documents of the late 18th – early 19th centuries, stored in federal and regional archives of Russia, as well as published materials, the article analyzes the reasons of the terminological mistake made in the biography of commander of Astrakhan’s Cossack regiment, major general P.S. Popov, which had been reproduced in the scientific works for longer than 100 years. So well known person in the Lower Volga region, P.S. Popov was purposefully chosen as an object of historical research. His biography is not typical for the people of provincial hereditary Russian nobility of this period, Astrakhan and Saratov’s nobility in this case, where, although rather conventionally, he was linked for a long time in the historical literature. Thanks to the current research, it was determined that P.S. Popov was born in Walachia, evidently not very rich noble family. For a long time he served in Bug Cossack regiment, where got promoted from Arnaut captain to officer rank. He took part in many campaigns of Russian-Turkish war, was repeatedly injured, and distinguished himself during the capture of the fortresses Ochakov and Ismail. P.S. Popov was awarded the order of St. John of Jerusalem, and golden mark for capture of Ismail. P.S. Popov was married to a daughter of Astrakhan priest, and had seven sons and daughters in this spousal. Already serving in Astrakhan province, he purchased a seigneury for himself and descendants in Tsaritsyn district of the Saratov province. His descendants settled in the Lower Volga region, kept the seigneury in possession, served in military and civil services.